Evaluation on Quality Attributes of Pectin Coated - Cassava Chips. (2019) - Khozaid, Nur 'Aisyah; Muhamad, Ida Idayu; Shaharuddin, Shahrulzaman
Abstract: Deep fried-based food is commonly consumed in Malaysia due to their tasty and good appearance of the food. However, high consumption of the food may lead to adverse effect to consumer's health beside high usage of oil-palm based cooking oil in deep frying process. Thus, this research aimed to investigate the effect of edible coating using different pectin concentration (1%, 2% or 3%) on cassava chips. Coated-cassava were prepared through dipping method into pectin and calcium chloride solution. Series of analysis such as lipid determination, texture analysis, colour determination, FTIR analysis, sensory evaluation and statistical analysis were conducted. Highest pectin concentration which 3% pectin-coated chips proved to reduce highest lipid uptake up to 11.750 ± 0.076 compared to uncoated chips (52.360 ± 0.762). For colour determination, it showed that the pectin coating did not changed the initial colour of the chips and enhanced the colour brightness after frying. Between all samples, the control or uncoated chips has the lowest result for hardness which was 577.216 ± 95.194 while 3% pectin coated chips had highest values in term of hardness which were 1338.209 ± 246.900. FTIR was able to recognize presence of the (N-O) group in all coated cassava chips compared to uncoated chips. The uncoated and pectin-coated chips had no significance different in overall acceptance in sensory analysis. This research concluded that edible coating from pectin with 3% concentration was able to reduce lipid uptake and enhanced several characteristics in cassava chips. Newly developed value-added coated cassava chips would offer a healthy, tasty and better appearance snack to consumer.